Instructional Music Videos: Their Effect on Reading Comprehension Skills among Struggling Readers - Pareñas, Sharonrose; Cabotaje, John Paul (Randwick International of Education and Linguistics Science Journal, 2025)
Reading comprehension plays a vital role in a student's success, and improving this skill is a key goal for teachers. This study investigates the effectiveness of using instructional music videos to help struggling readers at President Quirino National High School enhance their reading comprehension. The aim was to determine whether music videos could help students better understand and retain what they read. Before the intervention, the reading was valued of both Group A and Group B were fair. Group A had an average score of 15.76, while Group B scored slightly higher with 15.84 out of 30. After the instructional music videos were introduced, both groups took several tests to track their progress. Using ANOVA to analyse the data, the study found significant differences in the test scores of both groups. Group B, which was exposed to the music video intervention, showed a notable improvement, scoring higher than Group A. These findings suggest that instructional music videos can be an effective tool for improving reading comprehension skills. By using music videos, struggling readers were able to better engage with the material and increase their understanding. This study highlights the potential of incorporating multimedia tools in education to support students' learning and help them succeed in reading comprehension.